Self-assembly of monodispersed hierarchically porous Beta-SBA-15 with different morphologies and its hydro-upgrading performances for FCC gasoline1. Issue 32 (28th August 2015) - Gao, Daowei; Duan, Aijun; Zhang, Xin; Chi, Kebin; Zhao, Zhen; Li, Jianmei; Qin, Yuchen; Wang, Xilong; Xu, Chunming
<x xml:space="preserve">Abstract</x> Micro-mesoporous Beta-SBA-15 materials with platelet, sphere, short-rod and long-rod morphologies were in situ synthesized and used as the catalyst supports for hydro-upgrading of FCC gasoline.